Central nervous system infection in a pediatric population in West Java. - Dewi H Alisjahbana; Syndi Nurmawati; Mia Milanti; Hofiya Djauhari; Jeremy P Ledermann; Ungke Antonjaya; Yora Permata Dewi; Edison Johar; Ageng Wiyatno; Ida Yus Sriyani; Bachti Alisjahbana; Dodi Safari; et al. (Public Library of Science (PLoS), 2023)
Central nervous system (CNS) viral infections are critical causes of morbidity and mortality in children; however, comprehensive data on etiology is lacking in developing countries such as Indonesia. To study the etiology of CNS infections in a pediatric population, 50 children admitted to two hospitals in Bandung, West Java, during 2017-2018 were enrolled in a CNS infection study. Cerebrospinal fluid and serum specimens were tested using molecular, serological, and virus isolation platforms for a number of viral and bacteriological agents. Causal pathogens were identified in 10 out of 50 (20%) and included cytomegalovirus (n = 4), Streptococcus pneumoniae (n = 2), tuberculosis (n = 2), Salmonella serotype Typhi (n = 1) and dengue virus (n = 1). Our study highlights the importance of using a wide range of molecular and serological detection methods to identify CNS pathogens, as well as the challenges of establishing the etiology of CNS infections in pediatric populations of countries with limited laboratory capacity.